2019
DOI: 10.1093/jscr/rjz249
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing angiomatoid nodular transformation of the spleen: case report of a metastatic carcinoma-simulating disorder

Abstract: Sclerosing angiomatoid nodular transformation (SANT) is a rare nonneoplastic splenic disorder of unknown etiopathogenesis. This condition is usually found incidentally on imaging studies. Because of its similar features, SANT can wrongly be described as metastatic carcinoma. A 61-year-old Caucasian male was referred to our general surgery outpatient clinic regarding unusual splenic nodular formations in a routine abdominal ultrasound. All diagnostic exams performed confirmed metastatic splenic lesions, but no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Most patients with SANT are asymptomatic, with incidental findings of splenomegaly on physical examination or imaging performed for other unrelated conditions [ 4 , 8 ], as occurred in our patient, but some patients present with non-specific symptoms of abdominal pain, nausea, vomiting, anemia or malnutrition [ 5 , 9 , 10 ]. Our patient had chronic anemia not responding to dietary changes and iron supplementation.…”
Section: Discussionmentioning
confidence: 88%
“…Most patients with SANT are asymptomatic, with incidental findings of splenomegaly on physical examination or imaging performed for other unrelated conditions [ 4 , 8 ], as occurred in our patient, but some patients present with non-specific symptoms of abdominal pain, nausea, vomiting, anemia or malnutrition [ 5 , 9 , 10 ]. Our patient had chronic anemia not responding to dietary changes and iron supplementation.…”
Section: Discussionmentioning
confidence: 88%
“…Previously, there was no consensus on the nomenclature for this clinicopathological pattern. It was usually misdiagnosed as hemangioma, hemangiosarcoma, inflammatory pseudotumor, hamartoma ( 1 ), and even metastatic tumors ( 7 ). In 2004, Martel et al summarized the pathological features and defined it as SANT for the first time ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestation of SANT is asymptomatic or non-specific, with most lesions identified incidentally ( 5 ) or during the treatment of other unrelated diseases ( 6 ). Others exhibited featureless symptoms such as abdominal pain ( 7 ), nausea, vomiting, and malnutrition ( 8 ). Recently, Pelizzo et al reported a case of SANT with spontaneous mass rupture and intraperitoneal hemorrhage in a 9 week-old female infant ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The curative treatment for SANT is splenectomy [ 46 , [48] , [49] , [50] , [51] , [52] , [53] , [55] , [56] , [57] , [58] , [59] , [60] ]. Open splenectomy or minimally invasive splenectomy are both options for surgical treatment [ [62] , [63] , [64] , [65] , [66] , [67] , [68] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. In recent years, minimally invasive surgery such as robotic or laparoscopic splenectomy has become more popular due to a shorter hospital stay, less postoperative abdominal pain, and an early return to normal activity [ 18 , [63] , [64] , [65] , 78 ].…”
Section: Discussionmentioning
confidence: 99%